2012
DOI: 10.1186/1472-6882-12-239
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the hepatoprotective action of bear bile and coptidis rhizoma aqueous extract on experimental liver fibrosis in rats

Abstract: Aim of the studyBear bile and Coptidis Rhizoma have been used in Chinese medicine with a long tradition in treating heat-diseases. Both bear bile and Coptidis Rhizoma are used to treat liver diseases in clinical practice of Chinese Medicine. Since bears are currently endangered, it raises the question whether the use of bear bile is ethical. To look for substitute for bear bile, the aim of this study is to compare the anti-fibrotic effects of Coptidis Rhizoma and its major component berberine with the actions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…For example, Coptidis rhizome , a traditional Chinese medicinal plant used to clear heat and scavenge toxins, belongs to liver meridian in Chinese medicinal practice [ 149 , 150 ]. The effect of Coptidis rhizome and its bioactive compound berberine on CCl 4 -induced chronic and acute hepatotoxicity in rats has been thoroughly studied by our research group [ 10 , 30 , 127 ]. We have found that Coptidis rhizome might act as an antioxidant to relieve CCl 4 -induced oxidative stress and hepatic damage.…”
Section: Antioxidants For Prevention and Treatment Of Liver Diseasmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Coptidis rhizome , a traditional Chinese medicinal plant used to clear heat and scavenge toxins, belongs to liver meridian in Chinese medicinal practice [ 149 , 150 ]. The effect of Coptidis rhizome and its bioactive compound berberine on CCl 4 -induced chronic and acute hepatotoxicity in rats has been thoroughly studied by our research group [ 10 , 30 , 127 ]. We have found that Coptidis rhizome might act as an antioxidant to relieve CCl 4 -induced oxidative stress and hepatic damage.…”
Section: Antioxidants For Prevention and Treatment Of Liver Diseasmentioning
confidence: 99%
“…It is worth noting that vitamin E has been demonstrated clinically to be a rather promising drug for the treatment of non-alcoholic steatohepatitis [ 28 , 29 ]. Although data from clinical studies is yet to prove the efficacy of antioxidant, application of antioxidants is a rational curative strategy for prevention and treatment of liver diseases involving oxidative stress [ 17 , 30 ]. Natural antioxidants have been found in many edible (such as fruits, vegetables, cereals and tea) and medicinal plants, which often possess strong antioxidant and free radical scavenging abilities as well as anti-inflammatory action [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The further mechanism study showed that the anti-fibrosis effects by berberine may be induced by activation of AMPK, blockade of Nox4 and Akt expression [ 123 ]. A comparative research on the hepatoprotective action of bear bile and CRAE on experimental liver fibrosis in rats demonstrated that berberine, CRAE, and bear bile all exhibited anti-fibrotic properties on liver fibrosis [ 124 ]. All of these agents could remarkably increase the SOD activity and reduce the peroxidative stress in rat liver.…”
Section: Recent Research On the Roles Of Herbs And Phytochemicals mentioning
confidence: 99%
“…Rhizoma coptidis , commonly known as Huang Lian in China, has been one of the most important medicinal plants used for the treatment of various diseases in traditional Chinese medicine for more than 2000 years. In recent years, numerous scientific studies have demonstrated that Rhizoma coptidis and its main active constituents display a variety of activities including anti‐bacterial, anti‐cancer, anti‐hyperglycemic, anti‐hyperlipidemic, anti‐diabetic, anti‐obesity, anti‐inflammatory, radio‐protective and hepato‐protective effects . Moreover, Rhizoma coptidis and its isolated alkaloids have been reported to have cardio‐protective and neuro‐protective properties.…”
Section: Introductionmentioning
confidence: 99%